PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI, DAN LABA BERSIH TERHADAP HARGA SAHAM PADA MASA PANDEMI DI PERUSAHAAN BURSA EFEK INDONESIA (BEI) - Andres Putranta Sitepu; Fiona Fiona (Bajang Institute, 2023)
In manufacturing companies have a very important role because they are the basic ingredients needed by people on daily basis. Therefore, we need to know the dividend policy that investors get, the invesment decisions that investors can take, and how much net profit the company earned during the pandemic. The sample in this study consisted of 23 manufacturing companies with an observation period from 2020-2021. Sample selection using purposive sampling method. The analytical method used in this research is descriptive statistical and multiple linear regression analysis method. The data used is secondary data. The tool used to test the classic and hypothesis testing using Eviews 12. The results of this study indicate that the dividend policy,investment decisions, and net profit partially has a positive and significant effect on stock prices. Simultaneously, dividend policy, invesment decisions, and net profit have an effect on stock prices.